TINDAK PIDANA KORUPSI DENGAN MODUS MARK UP HARGA TIKET PESAWAT DALAM PELAKSANAAN PERJALANAN DINAS. (Studi di PT. Garuda Indonesia, Tbk Cto. Samarinda) - Hilaria Teresia (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTThis study aims to examine the factors of corruption mark up ticket trips using countries/regions budget, especially in the region of East Kalimantan.Official travel is an activity that is carried out by state officials/ government out of the position both in the country and abroad for the benefit of the country on the orders of the competent authorities, to the pricess of this journey almost always use air transport system, as a mode of transport which is considered very effective for the Republic of Indonesia is an acripelago, is considered effective because it has the characteristics of being able to move in a fast time. It’s just in the process of implementation of these official travel is sometimes used as a momentum by other people/person to commit fraud or irregularities commonly known service trips financial harm countries/regions for using state budget funds/regions.  The offial travel deviations among others is an act of Mark Up tiket.The goal of this research is to find out what kinds of corruption, and the more specific mode of action with Mark Up ticket in the implementatiton of official travel.            Results from this study indicate that is must needs be more effective solution to the problem of corruption, which is given administrative sanctions by the firm to the individual executing a business trip, and made official rules that determine the costing of services from the agency travel agent that provides service invoice transaction (Payments made after the implementation of official travel) so that no party travel agent who took the opportunity to provide the highest possible cost. Keyword : Coruption, mark up price